Post-Conflict Aceh; Partai Aceh Versus Partai Nanggroe Aceh at the 2017 Election - Saputra, Akmal; Nugroho, Heru; Sujito, Arie (Jurnal Ilmiah Peuradeun, 2022)
Post-conflict Aceh, GAM has transformed from a defense movement to a political movement. This transformation caused contestation in internal GAM. GAM versus GAM contestation in regional election contest has started since 2006, 2012, and 2017, but regional election contest in 2017 period is the peak of political fragmentation in Aceh. GAM has split into two local parties namely Partai Aceh (PA) and Partai Nanggroe Aceh (PNA). This article examined the strategy and basis of the two localparties inthe 2017 regional election contest (Pilkada). This article also revealed how these local parties establish an affiliation with the National Party in the 2017 regional election contest.This study used qualitative research methods and data collection techniques using in-depth interview techniques. The results showed that the Partai Aceh has a mass base at the grassroots as well as a militant mass (ex-combatants), while the Partai Nanggroe Aceh had a mass base of civilian GAM besides having a mass base at the grassroots (former combatants). The strategy carried out by each local party was to take religious leaders as symbolic capital to gain votes in the elections. Furthermore, the uniqueness of these two local partiesis they did not release ethnic ethnonationalism as symbols of its identity